The Effectiveness of DISTAD Learning Model on Metabolism Material for Critical Thinking Ability of High School Students - Siwi Pratiwi Prabandari; Siti Alimah (Universitas Negeri Semarang, 2023)
Class XII metabolic material has its own level of difficulty compared to other materials, because the material is difficult for the eye to perceive directly and involves a long process of enzymatic reactions. Metabolism learning at SMA Negeri 1 Karangkobar is less interactive causing students to be less critical in understanding material concepts. One alternative to improve critical thinking skills is the DISTAD Learning model (integration of the Discovery Learning model and the Student Teams Achievement Division model). The purpose of this study was to analyze the effectiveness of the DISTAD Learning model on metabolic material on high school students' critical thinking skills. This research is a quantitative research with the type of experimental research using the Pre-Experimental Design in the form of one group pretest-posttest design. The population of this study were students of class XII MIPA 1 to XII MIPA 5 SMA Negeri 1 Karangkobar for the academic year 2022/2023. Sampling was carried out using saturated sampling technique. The data collection technique used the test method and the students' critical thinking skills were tested with the One Sample T-test. The increase in students' critical thinking skills was seen from the average student score after participating in the DISTAD Learning model learning of 78.6 which was included in the high category with 76% of students obtaining grades ≥ KKM. Based on the calculation of the N-Gain test, there was an increase in three aspects of students' critical thinking skills, namely the aspect of giving simple explanations of 0.54, the aspect of making conclusions by 0.38, and the aspect of making further explanations of 0.61, where in the third This aspect shows the moderate category. In the analysis of the One Samples T-test showed a significance value of 0.000 (<0.05). The conclusion of this study is that the application of the DISTAD Learning model is effective in increasing the critical thinking skills of high school students.